2011
DOI: 10.2174/1874467211104020096
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Induced Non-targeted Response: Mechanism and Potential Clinical Implications

Abstract: Generations of students in radiation biology have been taught that heritable biological effects require direct damage to DNA. Radiation-induced non-targeted/bystander effects represent a paradigm shift in our understanding of the radiobiological effects of ionizing radiation in that extranuclear and extracellular effects may also contribute to the biological consequences of exposure to low doses of radiation. Although radiation induced bystander effects have been well documented in a variety of biological syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(111 citation statements)
references
References 61 publications
1
104
0
Order By: Relevance
“…If the COX-2 gene is causally linked to the bystander signaling pathways, it should be possible to modulate the bystander response using the specific inhibitor of COX-2 enzyme activity, NS-398. Although NS-398 treatment was able to reduce the hypoxanthine guanine phosphoryl transferase negative (HRPT-) mutant fraction in the directly irradiated cell population, the reduction of suppression was only 36% [217]. …”
Section: (4) Cell-cell Communication and Anticancer Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…If the COX-2 gene is causally linked to the bystander signaling pathways, it should be possible to modulate the bystander response using the specific inhibitor of COX-2 enzyme activity, NS-398. Although NS-398 treatment was able to reduce the hypoxanthine guanine phosphoryl transferase negative (HRPT-) mutant fraction in the directly irradiated cell population, the reduction of suppression was only 36% [217]. …”
Section: (4) Cell-cell Communication and Anticancer Treatmentmentioning
confidence: 99%
“…Activation of extracellular signal-related kinase (ERK) by phosphorylation is a key upstream event that precedes COX-2 expression [217]. Cell culture studies with and without PD98059, a specific MAPK-ERK inhibitor, showed suppression of the phosphorylated form of ERK in both, α-particle irradiated and bystander cells.…”
Section: (4) Cell-cell Communication and Anticancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In view of RIBE, existing radiotherapy models should be reconsidered and the carcinogenesis risk of low-dose radiation should be re-assessed. Therefore, a better understanding of the mechanisms underlying RIBE is essential.…”
Section: Introductionmentioning
confidence: 99%
“…These results are reminiscent of the GJIC-mediated propagation and amplification of cell death in glial cells during cerebral ischemia [20]. Similarly, GJIC contributes to the radiation "bystander effect" in which signaling molecules and/or reactive oxygen species induce damage in neighboring, non-irradiated cells [21] [22]. In contrast, GJIC may also reduce drug, ischemic, and radiation-induced cytotoxicity possibly by cell-cell sharing of protective molecules like glutathione [5] [23].…”
Section: Discussionmentioning
confidence: 98%